The Effect of Organizational Climate on Organizational Commitment in 2022: Case Study - Gaza Electricity Distribution Corporation - Swidan, Wasim Mohammed Jabir Hafez; Ali, Kalsom; Al-Tahitah, Ali Nasser (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to investigate the effect of organizational climate on organizational commitment in Gaza Electricity Distribution Corporation (GEDCO). A questionnaire was employed as the study tool, and a descriptive analytical technique was used to meet the study's objectives. (269) questionnaires were distributed, but (221) returned with a response rate of 82.16%. Also (SPSS) was used for data analysis by using various statistical methods. To analyze the structural equation model and look at the study hypotheses, analysis of a moment structures program (AMOS) tool was utilized. This study mainly contributes in enhancing the literature of the concept of organizational commitment, improving the methods of the study in the human resource area, and in finding out the effect of the research factors on organizational commitment. The results showed that there is a direct, weak, positive, effect of the organizational climate on organizational commitment (27.8%). The organizational structure (OS) dimension has the most impact on organizational commitment (74.4%), the next dimension was decision making (DM) equals (69.7%), while the dimensions (available technology (AT) was the least influential on organizational commitment (44.5%). The study recommends for providing employees with a proper awareness concerning organizational climate dimensions and how it may affect their organizational commitment.
Keywords: Organizational Climate; Organizational Commitment; GEDCO